Emergence of macrolide-resistant mycoplasma pneumoniae during an outbreak in a primary school: clinical characterization of hospitalized children - Hubert, Daniel; Dumke, Roger; Weichert, Stefan; Welker, Sybille; Tenenbaum, Tobias; Schroten, Horst (Pathogens, 2021)
Mycoplasma pneumoniae (M. pneumoniae) is a common causative pathogen of community-acquired pneumonia. Here, we report the development of macrolide resistance during a school outbreak of severe M. pneumoniae infections in southwest Germany. We conducted a case series to assess the clinical and laboratory characteristics of hospitalized children with M. pneumonia infection and the prevalence of macrolide-resistant M. pneumoniae (MRMP) in this patient group. We retrospectively analyzed 23 children with serologically (19 patients) and/or PCR (eight patients) confirmed M. pneumoniae infection between October 2019 and December 2019. Most of the 15 hospitalized patients had lower respiratory tract infection (n = 10) and required oxygen therapy (83%). The median length of hospitalization was 7 days (range 3-10 days). In 8/15 patients (53.3%) azithromycin and in 4/15 (26.6%) clarithromycin treatment was applied. However, among the five patients for which extended molecular characterization was performed, sequencing of 23S rRNA revealed no mutation only in the first case, but development of macrolide resistance A2058G in four subsequent cases. Hence, we identified a cluster of hospitalized patients with emerging MRMP. Further studies are warranted to confirm a potential link between macrolide resistance and disease severity.